Genome-wide association scan meta-analysis identifies three Loci influencing adiposity and fat distribution. - Cecilia M Lindgren; Iris M Heid; Joshua C Randall; Claudia Lamina; Valgerdur Steinthorsdottir; Lu Qi; Elizabeth K Speliotes; Gudmar Thorleifsson; Cristen J Willer; Blanca M Herrera; Anne U Jackson; Noha Lim; et al. (PLoS Genetics)
To identify genetic loci influencing central obesity and fat distribution, we performed a meta-analysis of 16 genome-wide association studies (GWAS, N = 38,580) informative for adult waist circumference (WC) and waist-hip ratio (WHR). We selected 26 SNPs for follow-up, for which the evidence of association with measures of central adiposity (WC and/or WHR) was strong and disproportionate to that for overall adiposity or height. Follow-up studies in a maximum of 70,689 individuals identified two loci strongly associated with measures of central adiposity; these map near TFAP2B (WC, P = 1.9x10(-11)) and MSRA (WC, P = 8.9x10(-9)). A third locus, near LYPLAL1, was associated with WHR in women only (P = 2.6x10(-8)). The variants near TFAP2B appear to influence central adiposity through an effect on overall obesity/fat-mass, whereas LYPLAL1 displays a strong female-only association with fat distribution. By focusing on anthropometric measures of central obesity and fat distribution, we have identified three loci implicated in the regulation of human adiposity.